Penerapan Siklus Plan-Do-Check-Action dalam Manajemen Mutu Terpadu di Lembaga Pendidikan - Dhita Ayu Astrellita; Bulqis (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2025)
Indonesia's Education in 2023 was ranked 67th out of 203 countries according to Worldtop20.org, indicating that the quality of education still requires significant improvement. One effective approach to enhance the quality of education is the implementation of the PDCA (Plan-Do-Check-Action) cycle. This cycle, a part of integrated quality management, involves planning, execution, evaluation, and follow-up corrective actions to achieve sustainable quality standards. This study uses the systematic literature review (SLR) method to analyze the implementation of PDCA in educational institutions. Out of 1,290 selected articles, four relevant articles were identified and analyzed. The results of the study indicate that the PDCA cycle improves educational quality through strategic planning, curriculum implementation, periodic evaluations, and corrective actions. However, the implementation of PDCA faces challenges such as limited teacher competencies, inadequate facilities and infrastructure, restricted funding, and difficulties adapting to new curricula. These challenges affect the effectiveness of the cycle in enhancing educational quality. Support from various stakeholders, including teacher training, facility improvements, and collaboration among stakeholders, is essential to optimize PDCA implementation. With a systematic and collaborative approach, the PDCA cycle enables educational institutions to enhance quality sustainably and remain competitive at the global level.